Influenza Clinical Diagnostic Testing and Antiviral Treatment among Children Hospitalized with Acute Respiratory Illness During the 2015–16 Influenza Season. (4th October 2017) - Campbell, Angela P; McGowan, Craig; Rha, Brian; Boom, Julie A; Englund, Janet; Halasa, Natasha B; Selvarangan, Rangaraj; Staat, Mary A; Weinberg, Geoffrey A; Azimi, Parvin H; Klein, Eileen J; McNeal, Monica; et al.
Abstract: Background: Although antiviral therapy is recommended for hospitalized patients with suspected or confirmed influenza, clinicians often rely on test results to determine management. Rapid influenza diagnostic tests (RIDTs) have suboptimal sensitivity; use of molecular assays may improve care. We evaluated clinical influenza testing and antiviral treatment practices in hospitalized children. Methods: Children aged <18 years with acute respiratory illness (ARI) were enrolled through active surveillance at 7 hospitals in the New Vaccine Surveillance Network between November 2015 and June 30, 2016; analysis was restricted to the influenza season. Preliminary data were analyzed for children who had clinical influenza diagnostic testing with a rapid influenza diagnostic test or molecular assay on nasopharyngeal or nasal swabs or nasal washes. Children who had received antivirals prior to hospitalization were excluded. Results: Of 2267 children, 1165 (51%) had clinical diagnostic testing on upper respiratory samples: 276 (24%) by RIDT alone, 780 (67%) by molecular testing alone, and 109 (9%) by both. The use of molecular testing alone varied by site, from 10% to 100% of samples tested. Of 116 (10%) children testing positive for influenza, 60 (52%) were treated; by site, treatment of children positive for influenza ranged from 25% to 83%. Antiviral treatment was given to 16/20 (80%) of those admitted ≤2 days from symptom onset vs. 44/96 (46%) children admitted >2 days after onset. Among 94 children tested by one method who were positive, >80% had samples collected in the emergency department or on day of admission, and 47 started treatment (Figure, A): 16/37 (43%) and 31/57 (54%) were treated when tested by RIDT alone and molecular testing alone, respectively. Of those positive children treated, 7/16 (44%) tested by RIDT vs. 22/31 (71%) by molecular testing started treatment on the day of testing (Figure, B). Conclusion: Half of hospitalized children with ARI who tested positive for influenza received antiviral treatment. Although there was high variability in testing and treatment by site, in positive patients who were treated the use of molecular testing appeared to be associated with prompt antiviral therapy. Understanding clinician reasons for relatively low treatment overall will require further investigation. Disclosures: J. Englund, Gilead: Consultant and Investigator, Research support Chimerix: Investigator, Research support Alios: Investigator, Research support Novavax: Investigator, Research support MedImmune: Investigator, Research support GlaxoSmithKline: Investigator, Research support N. B. Halasa, sanofi pasteur: Research Contractor, Research support Astra Zeneca: Research Contractor, Grant recipient